A nonhuman primate model for analysis of safety, persistence and function of adoptively transferred T cells - Berger, Carolina (2010)
BACKGROUND: Adoptive immunotherapy with antigen-specific effector T-cell (T(E)) clones is often limited by poor survival of the transferred cells. We describe here a Macaca nemestrina model for studying transfer of T-cell immunity. METHODS: We derived, expanded, and genetically marked CMV-specific CD8(+) T(E) clones with surface markers expressed on B cells. T(E) cells were adoptively transferred, and toxicity, persistence, retention of introduced cell-surface markers, and phenotype of the persisting T cells was evaluated. RESULTS: CD8(+) T(E) clones were efficiently isolated from distinct memory precursors and gene-marking with CD19 or CD20 permitted in vivo tracking by quantitative PCR. CD19 was a more stable surface-marker for tracking cells in vivo and was used to re-isolate cells for functional analysis. Clonally derived CD8(+) T(E) cells differentiated in vivo to phenotypically and functionally heterogeneous memory T-cell subsets. CONCLUSIONS: These studies demonstrate the utility of Macaca nemestrina for establishing principles for T-cell therapeutics applicable to humans.